2016
DOI: 10.1371/currents.dis.3a465b66f9327676d61eb8120eaa5499
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions, Programs and Strategies for Gender-based Violence Prevention in Refugee Populations: An Integrative Review

Abstract: Background: Gender based violence (GBV) remains one of the most serious threats to the health and safety of women and girls worldwide. The problem is even more pronounced in refugee populations where women and girls are at increased risk of violence. In 2015, UNHCR reported the highest number of forcibly displaced people in recorded history. Despite growing need, there have been few rigorous evaluations of interventions aimed at primary GBV prevention and no systematic reviews of GBV prevention efforts specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 26 publications
2
59
0
Order By: Relevance
“…40 One promising strategy is the use of short films and video projects in order to educate the local community and to initiate a public discussion about GBV and SV. [41][42][43] One multi-year participatory video project rated as being of weak quality, which took place in Thailand along the Thai-Myanmar border and in Rwanda, Liberia, South Sudan and Uganda in Africa, actively engaged the community and included different stakeholders such as ministries, religious leaders and youth and women's groups in the creation of several targeted videos, which educated about GBV, including SV. 40 Each public screening was then followed by reflective discussions.…”
Section: Education and Trainingmentioning
confidence: 99%
See 4 more Smart Citations
“…40 One promising strategy is the use of short films and video projects in order to educate the local community and to initiate a public discussion about GBV and SV. [41][42][43] One multi-year participatory video project rated as being of weak quality, which took place in Thailand along the Thai-Myanmar border and in Rwanda, Liberia, South Sudan and Uganda in Africa, actively engaged the community and included different stakeholders such as ministries, religious leaders and youth and women's groups in the creation of several targeted videos, which educated about GBV, including SV. 40 Each public screening was then followed by reflective discussions.…”
Section: Education and Trainingmentioning
confidence: 99%
“…40 In a qualitative study in Rwanda, refugees also expressed the need for collaboration between camp leaders, local communities and NGOs to avoid a top-down intervention approach and thereby increase accountability, ownership and acceptability of protective services. 43 One intervention of weak quality in a refugee camp in Darfur showed that actively consulting and engaging female refugees and camp leaders in developing solutions to safety concerns was more effective and sustainable than endeavouring to enforce existing guidelines and policies. 44 Another article by Spangaro et al 41 found that SV interventions designed and implemented with active involvement of the community were associated with greater reductions in SV exposure and incidence, concluding that engagement of targeted communities may be fundamental to the success and sustainability of SV prevention efforts.…”
Section: Education and Trainingmentioning
confidence: 99%
See 3 more Smart Citations